ANALISIS PENYERAPAN TENAGA KERJA PADA USAHA PERCETAKAN FOTO COPY DI KOTA KENDARI - Takyuddin, Muh. (JURNAL EKONOMI UHO, 2016)
This study aims to determine workers absorbed on  printing business in Kendari. The study used  primary  data with 10  sample of printing business.   This study used  descriptive analysis. Based on the results and discussion show that   workers absorbed  on  10 business printing is 70 workers. The wages offered by a photo copy printing business in Kendari is lower than  the regional minimum wages. The lower wage  does not affect on worker  behaviour to labor supply